Pengaruh Penghayatan Nilai-nilai Pancasila terhadap Sikap Moderasi Beragama pada Siswa Kelas XI IPS SMA Negeri 1 Tomohon - Marthinus Marcel Lintong; Ryan Gabriel Kilis (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
This research was aimed to explore the influence of appreciating Pancasila’s values to the attitude of religious moderation among students in SMA Negeri 1 Tomohon. This research was carried on April 2022 in SMA Negeri 1 Tomohon. Primary data was collected through questionnaires to 57 students of the school. The method of this research was quantitative using descriptive statistics. Three hypotheses were tested by multiple linear regresseion analysis. The result of this study showed that three hypotheses were proven to have correlation significantly. It was proven by the result of statistical account through simple linear regression analysis. So the main conclusion of this research was to find significant correlation between the appreciation of Pancasila’s values (x variable) and the attitude of religious moderation (y variable).